Humoral and cellular immune responses to Pfizer-BioNTech BNT162b2 SARS-CoV-2 vaccine in adolescents with liver transplantation: Single center experience - Sánchez-Zapardiel, Elena; Alós, María; Nozal, Pilar; González-Muñoz, Miguel; Frauca-Remacha, Esteban; Gavilán, Lucía Blanca; Quiles, María José; Hierro, Loreto; López-Granados, Eduardo (Frontiers in Immunology, 2022)
Background. Immune responses to vaccines against severe acute respiratory syndrome (SARS)-coronavirus (CoV)-2 are variable. In the absence of disease, youngsters are expected to better react to vaccines than adults. Nevertheless, chronic immunosuppression in transplant recipients may impair their capability to generate protection. We aim to explore immune responses after BNT162b2 SARS-CoV-2 vaccination in our cohort of young liver-transplanted patients. Methods. A prospective study of adolescent liver-transplanted patients (n=33) in the long-term follow-up was performed. Immune responses after receiving Pfizer-BioNTech BNT162b2 vaccine were analyzed at two time-points: baseline and 30 days after the second dose. Humoral responses were measured by fluoroenzyme-immunoassay and T-cell responses by interferon--release assay. Post-vaccine coronavirus disease (COVID-19) events were recorded by a survey. Results. Pre-vaccine SARS-CoV-2-specific antibodies were undetectable in 27/32 (84.4%), negative/indeterminate in 3/32 (9.4%) and positive in 2/32 (6.3%) patients. Cellular responses at baseline were negative in 12/18 (66.6%), positive in 3/18 (16.6%) and indeterminate in 3/18 (16.6%) recipients. None of the baseline positives recalled any symptoms. Post-vaccine antibodies were detected in all patients and 92.6% showed levels >816 BAU/mL. Twenty (71.4%) recipients had positive T-cell responses. Regarding post-vaccine SARS-Cov-2 infection, 10 (30.3%) patients reported COVID-19 without hospitalization and 21 (63.6%) did not notify any infection. Negative and positive cell-response groups after vaccination showed statistically significant differences regarding COVID-19 cases (62.5% vs 22.2%, respectively; p=0.046). Conclusions. Adolescents and young adults with liver transplantation responded to SARS-Cov-2 vaccine, generating both humoral and cellular responses. Recipients developing cellular responses after vaccination had a lower incidence of COVID-19.